PENGARUH LINGKUNGAN MINYAK MENTAH TERHADAP LAJU KOROSI PADA PIPA BAJA KARBON DAN PIPA GALVANIS - Syafrul Hadi; Jumarlis Jumarlis (LP2M - Institut Teknologi Padang, 2013)
In oil industry and gas, pipeline constituting main component that is utilized as medium of distribution and oil transmission, gas and good water at continent (onshore) and also at offshore (offshore). Rock oil (Crude oil ) a new one taken from by earth belly consisting of 3 main compositions which is oil,gas and water. Meaty alone rock oil of various chemical element kinds, generally mixed organic( hydrocarbon), oxygen, sulphur and nitrogen, water, salt, H2 S and mixed another organic. About problem which often been faced by pipeline on offshore (offshore) and land (onshore) in industry oil and gas is its happening corrosion. To the effect this research is subject to be know rock oil environment influence to corrosion fast carbon steel pipe and galvanic, well is seen from visual's watch and also of outgrows it happening corrosion runaway speed. pengorosian's process carbon steel pipe and galvanic pipe is done in rock oil medium with hall temperature 29 38O C. Of corrosion watch result and corrosion fast both of sample, visually that soaking time afters specimen 36th day until 47 th day, specimen experiences surface corrosion that merata. Its happening is this discoloration as a corrosion product form merata (karat). There is product even the other corrosion be been formed it sumuran's corrosion by marks sense little fleck. Meanwhile sample corrosion runaway speed greater galvanic pipe fast corrosion namely 0,2996 mpy of on carbon steel pipe sample 0.1242 mpy. It because of marks sense proprietary chemical element rock oils, its main h2 N, H2 O, CO2 , O2 one that so aggressive, where is element h2 N, H2 O, CO2, O2 this if contact with Fe will hasten its happening corrosion.